Implementation of Rescheduling as an Effort to Rescue Non Performing Financing in Rahn Tasjily Contracts at BMT Al Hikmah - Eri Susanti; Miswan Ansori (CV. Ulil Albab Corp, 2024)
Distribution of financing to members even though it has passed the 5 C analysis (Character, Capacity, Collateral, Capital, Condition) does not eliminate the possibility of problematic financing. BMT Al Hikmah's efforts to rescue problematic financing through non-litigation and litigation channels. This research examines financing settlement using a non-litigation process, namely, the mechanism for rescheduling problematic financing with the rahn tasjily agreement at BMT Al Hikmah as well as examples of cases of implementing rescheduling. The type of research used is by conducting research directly in the field (field research). Data collection techniques include interviews, collecting documents needed to dig up information, and direct observation. The data analysis technique is descriptive qualitative. The analysis results show that rescheduling provides relief to members by extending the payment period, with the aim that members can still pay their financial obligations without excessive pressure by considering members' income and abilities. The rescheduling process involves two mechanisms, namely by members who have good faith by visiting BMT Al Hikmah to carry out rescheduling and the second method is by the Account Officer (AO) when members do not have good faith, by visiting members directly to offer financing settlement options by rescheduling . This research also explains a concrete example that provides an overview of how rescheduling is implemented in practice.